(untitled) (American Journal of Islam and Society, 2015)
Perhaps no single historical occurrence looms larger in the imagining of contemporary Iranian identity than Islam’s rise and the ensuing widespread conversions on and around the Iranian plateau. Of course, as with any events occurring over a millennium ago, not to mention events that have shaped their heirs’ confessional commitments, one encounters a gulf between how Iran’s Muslim conversion is written in the popular imagination and how historiographical studies attempt to make sense of such complex transformations. Nonetheless, Sarah Bowen Savant’s The New Muslims of Post-Conquest Iran: Tradition, Memory, and Conversion might ultimately shape Iranian and Islamic studies not only by contributing novel scholarship to the field, but also by speaking to non-specialists’ interests as well. As evidence of popular interest, one need only note the continual reprints of Abd al-Husayn Zarrinkub’s seminal 1957 study, Dū Qarn Sukūt (Two Centuries of Silence), which considers the period following the Islamic conquest and the Sasanian Empire’s collapse. Savant’s study picks up where Zarrinkub’s ends, arguing that post-conquest Iranians experienced a twofold conversion during the ninth to eleventh centuries: becoming both Muslim and Persian. And while the author disavows simplistic notions like historical silence or static national identities, her book, like Zarrinkub’s, sheds new light on Persian Muslim identities in a particular historical context and suggests how they are formed, negotiated, contested, and transformed over time and space ...